2020
DOI: 10.1186/s12903-020-1025-9
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric analysis evaluating apical microleakage in retrograde filling using GIC, MTA and biodentine: an in-vitro study

Abstract: Background: The present study compares the apical microleakage of three different root-end filling materials in which the retrograde cavity is prepared by two different burs. Methods: Eighty extracted single rooted maxillary and mandibular premolars were taken. Root canal treatment was completed. Apical 3 mm of all the teeth were resected with diamond disk. The tooth were divided into four groups with two subgroups for each group containing 10 tooth (N = 10) as: Group IA (Negative Control and IB (Positive Cont… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…As part of modern endodontic surgery protocols, a variety of retrograde filling materials are used, such as intermediate restorative material (IRM) [3], mineral trioxide aggregate (MTA) [4], and Biodentine [4].…”
Section: Introductionmentioning
confidence: 99%
“…As part of modern endodontic surgery protocols, a variety of retrograde filling materials are used, such as intermediate restorative material (IRM) [3], mineral trioxide aggregate (MTA) [4], and Biodentine [4].…”
Section: Introductionmentioning
confidence: 99%
“…Both materials used in this study as apical plugs showed similar attachment of osteoblast cells on their surfaces [18] and significant antimicrobial effect against E. faecalis [19]. In addition, they showed good marginal adaptation and similar sealing ability [20,21]. The thickness of the apical plug plays an important role in maintaining an adequate apical seal.…”
Section: Discussionmentioning
confidence: 86%
“…Contrarily, the dye extraction technique used in this study recovers all of the dye that leaked through the apex by dissolving it in acid, thus avoiding the drawbacks of sectioning the root. It also quantitatively measures the optical density of the solution by using a spectrophotometer, thus producing accurate results for the microleakage studies [46,47]. The lowest microleakage was reported for the endodontic pressure syringe group, with significant difference with that of the modified disposable syringe and the reamer technique.…”
Section: Discussionmentioning
confidence: 99%